Thalamotomy-Like Effects From Partial Removal of a Ventral Intermediate Nucleus Deep Brain Stimulator Lead in a Patient With Essential Tremor: Case Report. Issue 5 (21st July 2015) - Rolston, John D.; Ramos, Alexander D.; Heath, Susan; Englot, Dario J.; Lim, Daniel A.
Abstract: BACKGROUND AND IMPORTANCE: The ventral intermediate nucleus of the thalamus is a primary target of deep brain stimulation (DBS) in patients with essential tremor. Despite reliable control of contralateral tremor, there is sometimes a need for lead revision in cases of infection, hardware malfunction, or failure to relieve symptoms. Here, we present the case of a patient undergoing revision after ventral intermediate nucleus (Vim) DBS failed to control his tremor. During the electrode removal, the distal portion of the lead was found to be tightly adherent to tissue within the deep brain. Partial removal of the electrode in turn caused weakness, paresthesias, and tremor control similar to the effects produced by thalamotomy or thalamic injury. CLINICAL PRESENTATION: A 48-year-old man with essential tremor had bilateral Vim DBS leads implanted 10 years earlier but had poor control of his tremor and ultimately opted for surgical revision with lead placement in the zona incerta. During attempted removal of his right lead, the patient became somnolent with contralateral weakness and paresthesias. The procedure was aborted, and postoperative neuroimaging was immediately obtained, showing no signs of stroke or hemorrhage. The patient had almost complete control of his left arm tremor postoperatively, and his weakness soon resolved. CONCLUSION: To the best of our knowledge, this is the first reported case of cerebral injury after DBS revision and offers insights into the mechanism of high-frequency electric stimulation compared with lesions. That is, although high-frequency stimulation failed to control this patient's tremor, thalamotomy-like injury was completely effective.